Rehabilitation of an Internet network in 40 schools in Nabón, Ecuador - Cabrera-Tituana, Ronny Israel (2021)
Internet access is necessary to ensure respect for the right to education, however, worldwide about 75% of school-age children in rural areas do not have access to the Internet at home, which makes it imperative the need for actions to reduce the digital gap to improve the quality of education in rural communities in Ecuador. This article describes the rehabilitation of an Internet network of 40 schools in the Nabón community, Ecuador. An earlier initiative implemented the Internet network, but lack of maintenance left it non-functional. With the support of the Municipality of Nabón, Motorola Foundation and IEEE SIGHT, a group of volunteers from IEEE Ecuador evaluated the state of the network to identify opportunities using the existing infrastructure. The commitment to the community, as well as the development of capacities, are at the center of the intervention to guarantee the sustainable development of the project. This document reports on the design, implementation, achievements and lessons learned from the rehabilitation of the Internet network.